Adding Value to The Recruitment of Senior Health Service Managers: A participatory action research study - Kathryn Gregory; Pieter Van Dam; Lindsay Smith (Asia Pacific Journal of Health Management)
Objective: As healthcare services evolve, effective management is essential to ensure they remain contemporary, function effectively, deliver client-centered care, foster a positive culture, support staff, drive strategic direction and promote continuous quality improvement. Health managers strongly influence and drive the services they are responsible for, therefore appointing the right person is essential. This qualitative Participatory Action Research (PAR) study explores the values prioritised by health services in recruiting senior managers and collaboratively develops actionable solutions to enhance these crucial recruitment processes.